Pelatihan Learning Management System Moodle bagi MGMP Matematika SMP Kabupaten Tasikmalaya - Mega Nur Prabawati; Eva Mulyani; Muhamad Zulfikar Mansyur; Eko Yulianto (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2023)
Sophisticated technology makes many people make innovations, especially in the field of education. The application of information technology to support the educational process has become a necessity for educational institutions in Indonesia. Utilization of information technology is very much needed to increase efficiency and productivity for education management. The application of technology in the field of education that is currently still being developed is the Learning Management System (LMS). LMS or better known as Learning Management System is a software for administration, documentation, activity reports, teaching and learning activities and online activities (connected to the internet), E-learning and training materials. One of the LMS that is open source and has the most users worldwide is the Moodle LMS (Modular Object Oriented Dynamic Learning Environment).